Interferences of Minangkabau-Indonesian EFL Students' Dialogues: A Result of Double Language Transfer - Shally Amna (JURNAL ARBITRER, 2018)
Learning English as a foreign language is a long journey of language transfer for students in West Sumatera, Indonesia. When the students learn to produce a sentence in English, they often use double language transfers, that is, from Minangkabau language as their native language to Indonesian language as their national language and from Indonesian language to English Language. Furthermore, the effect of literal translation which is used as mainly method in the process of learning languages at schools worsen the students' errors and mistakes in learning English language. This research seeks to investigate the interferences in English Conversation scripts made by students of UPI YPTK Padang who were assigned to create a conversation in groups to certain topics. The results of the lexical and syntactical interferences found in the scripts indicated that the students are struggling with noun-verb confusion, subject matters, word choices, tenses, and non-existence forms of auxiliaries in L1. The findings provide insight into English learning and teaching techniques and present suggestions for lectures and materials developers.